2011
DOI: 10.3109/02770903.2011.616254
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Follow-Up of Early Intensive Self-Management Guidance in Newly Diagnosed Patients with Asthma

Abstract: The effectiveness of intensive self-management education could be shown only in the short term. The groups did not differ significantly in any of the parameters investigated, and showed nearly normal LF and HRQoL. AHR improved only partly and only a minority of the patients had asthma under good control according to GINA criteria. This study showed that evaluation of asthma using LF alone does not show the whole truth about asthma treatment results. HRQoL should be used in conjunction with GINA criteria, to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…points. (11) Although it have been suggested that self-management effectiveness is reduced when assessed over long-term follow-up (24), this study showed that patients had a good compliance and asthma control has been improved in a period over one year. A possible explanation for this situation could be the fact that the patients knew they were in a study and that they had to come for re-evaluation every three months, while in the study of Kauppinen et al, the patients were assessed for a much longer period (> 10 years).…”
Section: Discussionmentioning
confidence: 54%
“…points. (11) Although it have been suggested that self-management effectiveness is reduced when assessed over long-term follow-up (24), this study showed that patients had a good compliance and asthma control has been improved in a period over one year. A possible explanation for this situation could be the fact that the patients knew they were in a study and that they had to come for re-evaluation every three months, while in the study of Kauppinen et al, the patients were assessed for a much longer period (> 10 years).…”
Section: Discussionmentioning
confidence: 54%
“…No data was reported on mortality, asthma control or annual FEV 1 decline. patients were found to be in control after ten years of follow-up [36]. In the study of Porpodis et al, 225 asthma turned out to be milder after 12 years of follow-up in the majority of patients (see Table 2B) 226 [37].…”
mentioning
confidence: 93%
“…In the study of 299 Porpodis et al, the severity of asthma turned out to be milder after 12 years of follow-up but 34% of 300 the patients were still considered to have either moderate or severe asthma [37]. In a Finnish study 301 [36] of new-onset asthma diagnosed at adult age, 76% of asthmatics were not in control after ten …”
mentioning
confidence: 96%
“…Despite many self-management programs that have been developed for both adults 1120 and children 2127 in the past 3 decades, results have been mixed in terms of success. 28,29 At the same time, it is also important to recognize the effect of other comorbidities and how they could affect the effectiveness of these interventions.…”
Section: Introductionmentioning
confidence: 99%